Use of preoperative computed tomography for surgical treatment of recurrent draining tracts. (11th December 2013) - Bouabdallah, R.; Moissonnier, P.; Delisle, F.; De Fornel, P.; Manassero, M.; Maaoui, M.; Fayolle, P.; Viateau, V.
<x xml:space="preserve">Abstract</x> OBJECTIVES To evaluate a rational decision‐making approach based on preoperative computed tomography for surgical planning in dogs and cats with recurrent draining tracts. METHODS Retrospective evaluation of case records of animals that underwent preoperative computed tomography for surgical treatment of thoracic/abdominal recurrent draining tracts. Cases were classified according to whether a source of inflammation and/or infection, in particular foreign bodies, was identified (group 1), suspected (group 2) or neither identified nor suspected (group 3) at computed tomography. Surgery consisted of removal of the source of inflammation and/or infection (group 1), debridement or abscess drainage (group 2) or en bloc resection of diseased tissues (group 3). Clinical outcome was evaluated at least 12 months after surgery. RESULTS A source of inflammation and/or infection was found in 100% (8 of 8), 41% (7 of 17) and 25% (3 of 12) of cases in groups 1, 2 and 3, respectively. Recurrent draining tracts resolved in 100% (8 of 8), 94% (16 of 17) and 92% (11 of 12) of cases in groups 1, 2 and 3, respectively. CLINICAL SIGNIFICANCE The proposed strategy provided a 95% (35 of 37) cure rate, after a single procedure in 81% (30 of 37) of cases. Recovery of a foreign body at surgery was not a prerequisite for the resolution of the recurrent draining tracts.